1971
DOI: 10.1017/s0025727300016148
|View full text |Cite
|
Sign up to set email alerts
|

WILLIAM CULLEN: HIS CALIBRE AS A TEACHER, AND AN UNPUBLISHED INTRODUCTION TO HIS A TREATISE OF THE MATERIA MEDICA, LONDON, 1773

Abstract: Texts and Documents WILLIAM CULLEN: HIS CALIBRE AS A TEACHER, AND AN UNPUBLISHED INTRODUCTION TO HIS A TREATISE OF THE MATERIA MEDICA, LONDON, 1773. WHILE THE main purpose of this paper is to make readily available Cullen's introduction to his first (1761) Edinburgh materia medica course, some characteristics of Cullen's teaching, which was possibly the most significant in eighteenth-century British medical education, will also be considered. Cullen's 1761 materia medica course-omitting the introduction-was pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In the winter of 1760-1761, following the death of the professor of materia medica, Alston, Cullen gave the materia medica lectures for one year only. The lectures were much appreciated by the students; copies of the lecture notes began to circulate widely and in 1772 appeared in print in London without Cullen's consent (6)(7)(8)(9)(10).…”
Section: The Second Generation Of Teachers Of Medical Sciencesmentioning
confidence: 99%
“…In the winter of 1760-1761, following the death of the professor of materia medica, Alston, Cullen gave the materia medica lectures for one year only. The lectures were much appreciated by the students; copies of the lecture notes began to circulate widely and in 1772 appeared in print in London without Cullen's consent (6)(7)(8)(9)(10).…”
Section: The Second Generation Of Teachers Of Medical Sciencesmentioning
confidence: 99%
“…With the observation of Thomas Willis in 1674 that the residue of the evaporated urine of diabetics tasted sweet “as if imbued with honey (quasi melle) and sugar” began the deciphering of the etiology of this ancient disease (56,57). His argument that diabetes is not a disease of the retentive powers of the kidney as it had been considered theretofore, but one of the blood in which sweetness is delivered to the kidney, was established by the meticulous studies of Matthew Dobson (1732–1784) who demonstrated in 1776 the presence in the blood and urine of diabetics the same saccharine material, ultimately characterized as glucose in 1817.…”
Section: Chemistrymentioning
confidence: 99%
“…His argument that diabetes is not a disease of the retentive powers of the kidney as it had been considered theretofore, but one of the blood in which sweetness is delivered to the kidney, was established by the meticulous studies of Matthew Dobson (1732–1784) who demonstrated in 1776 the presence in the blood and urine of diabetics the same saccharine material, ultimately characterized as glucose in 1817. In conducting his studies, Dobson had consulted the chemist William Cullen (1710–1790), who in 1769 called attention to polyuric patients in whom the urine was insipid in taste, and added the descriptive adjective “mellitus” to the diabetes described by Willis over a century earlier (56,57). The definition and classification of polyuria was clarified further in 1794 by Johann Peter Frank (1745–1821) who subdivided it into true for diabetes mellitus and spurious or false for diabetes insipidus (58).…”
Section: Chemistrymentioning
confidence: 99%
“…6 He used the Linnean system of classification of plants 'as the only method of arriving at a distinct knowledge of them' and the students, knowing the name, were 'enabled to know, by the class, its properties'. 7 In the main, Cullen followed the system that Linnaeus used in his materia medica although he considered that, at times, Linnaeus extended his system too far.…”
Section: Carl Linnaeus (1707 -78) and The Classification Of Animal Anmentioning
confidence: 99%